Space-saving Sample Preparation Procedure to Monitor Residual Canthaxanthin in Hen Egg Yolk - Furusawa, Naoto (Emerging Challenges in Agriculture and Food Science Vol. 4, 2022)
This chapter introduces a suitable analytical method for routine residue monitoring of antimicrobial drugs in food. A simplified and space-saving technique of sample preparation followed by an isocratic mobile phase high-performance liquid chromatography (HPLC) coupled diode array detector for quantifying canthaxanthin (CX), colouring agent, in hen egg yolk was described here. The analyte was extracted from the sample using a handheld ultrasonic homogenizer with 0.6 ml solvent, and purified by a normal-phase InertSep® CN mini-syringe column. The total time and solvent consumption required for the analysis of a single sample were < 1h and < 7 ml, respectively. The method validation data (linearity, accuracy, precision, and system suitability) are well within the international method acceptance criteria. The procedure may be proposed as a standardized analytical method for the routine residue monitoring of CX in hen egg yolk.